2014
DOI: 10.3390/molecules19044212
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic and Theoretical Studies of New Quaternary N,N-Dimethyl-3-phthalimidopropylammonium Conjugates of Sterols and Bile Acids

Abstract: New quaternary 3-phthalimidopropylammonium conjugates of steroids were obtained by reaction of sterols (ergosterol, cholesterol, cholestanol) and bile acids (lithocholic, deoxycholic, cholic) with bromoacetic acid bromide to give sterol 3β-bromoacetates and bile acid 3α-bromoacetates, respectively. These intermediates were subjected to nuclephilic substitution with N,N-dimethyl-3-phthalimidopropylamine to give the final quaternary ammonium salts. The structures of products were confirmed by spectral ( 1 H-NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 51 publications
0
9
0
14
Order By: Relevance
“…It was natural that no band was found in the 2950–2850 cm −1 region of the spectra of polyphenols, and the bands at this region in the spectra of polyphenol–cholate coprecipitates indicated the presence of cholates. The symmetric CO stretching vibrations were responsible for the non‐symmetrical peaks in the range from 1716 to 1699 cm −1 in the spectra of polyphenols, while the peaks in the 1614–1615, 1532–1541, 1446–1448 cm −1 regions were assigned to the aromatic ring stretching vibrations. Furthermore, the symmetric and asymmetric –COO − stretching vibrations were associated with the bands at 1568–1576 and 1408 cm −1 in the spectra of cholates .…”
Section: Resultsmentioning
confidence: 99%
“…It was natural that no band was found in the 2950–2850 cm −1 region of the spectra of polyphenols, and the bands at this region in the spectra of polyphenol–cholate coprecipitates indicated the presence of cholates. The symmetric CO stretching vibrations were responsible for the non‐symmetrical peaks in the range from 1716 to 1699 cm −1 in the spectra of polyphenols, while the peaks in the 1614–1615, 1532–1541, 1446–1448 cm −1 regions were assigned to the aromatic ring stretching vibrations. Furthermore, the symmetric and asymmetric –COO − stretching vibrations were associated with the bands at 1568–1576 and 1408 cm −1 in the spectra of cholates .…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29][30] Numerous theoretical studies on electronic structure using the density functional theory (DFT) with most popular hybrid functional (B3LYP) in chemistry to study the structure and reactivity of the cholestane or steroidal family containing various steroidal skeletal functionalities have been reported previously. [31][32][33] An earlier study has convincingly demonstrated the high accuracy and concordance between DFT methods and experimental results for steroid compounds. This suggests that the DFT/ B3LYP method is suitable for future studies on steroidal nitroolefins.…”
Section: Introductionmentioning
confidence: 91%
“…Functional Density Theory (DFT) is a collection of techniques for calculating electronic structures in quantum mechanics with a wide range of applications for organic and complicated systems such as steroidal skeletons . Numerous theoretical studies on electronic structure using the density functional theory (DFT) with most popular hybrid functional (B3LYP) in chemistry to study the structure and reactivity of the cholestane or steroidal family containing various steroidal skeletal functionalities have been reported previously . An earlier study has convincingly demonstrated the high accuracy and concordance between DFT methods and experimental results for steroid compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In the second step, 3β-bromoacetates have been treated with tertiary alkylamines (CH3-(CH2)n-N(CH3)2, n = 8-14) under SN2 reaction conditions to give conjugates of ergosterol (106-109), cholesterol (110-113), and cholestanol (114-117) ( Figure 6). The authors also obtained a series of N,N-dimethyl-3-phthalimidopropylammonium conjugates of sterols (ergosterol, cholesterol, cholestanol) (118-120) and bile acids (lithocholic, deoxycholic, cholic) (121-123) (Figure 7) [50]. The synthesis and physicochemical properties of quaternary N,N-dimethyl-3-phthalimidopropylammonium conjugates of ergosteryl 3β-bromoacetate, cholesteryl 3β-bromoacetate, and dihydrocholesteryl 3β-bromoacetate, as well as methyl litocholate 3α-bromoacetate, methyl deoxycholate 3α-bromoacetate, and methyl cholate 3α-bromoacetate with N,N-dimethyl-3-phthalimidopropylamine in acetonitrile were investigated and described.…”
Section: Quaternary Alkylammonium Conjugates Of Steroidsmentioning
confidence: 99%
“…The synthesis and physicochemical properties of quaternary N,N-dimethyl-3-phthalimidopropylammonium conjugates of ergosteryl 3β-bromoacetate, cholesteryl 3β-bromoacetate, and dihydrocholesteryl 3β-bromoacetate, as well as methyl litocholate 3α-bromoacetate, methyl deoxycholate 3α-bromoacetate, and methyl cholate 3α-bromoacetate with N,N-dimethyl-3-phthalimidopropylamine in acetonitrile were investigated and described. The authors also obtained a series of N,N-dimethyl-3-phthalimidopropylammonium conjugates of sterols (ergosterol, cholesterol, cholestanol) (118-120) and bile acids (lithocholic, deoxycholic, cholic) (121-123) (Figure 7) [50]. The synthesis and physicochemical properties of quaternary N,N-dimethyl-3-phthalimidopropylammonium conjugates of ergosteryl 3β-bromoacetate, cholesteryl 3β-bromoacetate, and dihydrocholesteryl 3β-bromoacetate, as well as methyl litocholate 3α-bromoacetate, methyl deoxycholate 3α-bromoacetate, and methyl cholate 3α-bromoacetate with N,N-dimethyl-3-phthalimidopropylamine in acetonitrile were investigated and described.…”
Section: Quaternary Alkylammonium Conjugates Of Steroidsmentioning
confidence: 99%